Перспективы развития биотехники в отечественном протезировании - Салеева, А. Д.; Семенець, В. В. (ХНУРЭ, 2002)
The software for microprocessor system for control of above-elbow prosthesis was developed. The design of elbow unit drives was improved. A training seat for the patient was developed.
Keywords: протезирование; интеллектуальные узлы протезов; специализация; биотехнические аппараты